Commodification of Disability in Digital CSR Campaigns: Semiotic and Reseption Analysis VCD Students - Nurul Fadhillah S; Sri Riski Wulandari (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the commodification of disability in digital Corporate Social Responsibility (CSR) campaigns and map the reception patterns among Visual Communication Design (VCD) students. Adopting a descriptive qualitative approach, the study employs a multistage analysis integrating Roland Barthes’ semiotics on five CSR campaign videos; Pertamina, Tokopedia, Indodax, BRI Insurance, and Alfamidi, alongside Stuart Hall’s reception theory through reflective discussions with 24 VCD students at Universitas Negeri Makassar. The findings reveal that CSR videos systematically naturalize disability as an emotional commodity, portraying subjects as